Analisis Pelaksanaan Asistensi Mengajar FKIP Universitas Riau Ilmu Fisika di MA Darul Hikmah - Septia, Audy (Penerbit Goodwood, 2024)
This study aimed to examine and analyze the effectiveness of the implementation of the Teaching Assistance Program for the Merdeka Belajar Campus Merdeka (MBKM) Faculty of Teacher Training and Education (FKIP) University of Riau at the MA Darul Hikmah School Pekanbaru in an effort to improve the quality of learning and graduates in the tertiary environment and to identify the obstacles that arise. arises from the implementation of Teaching Assistance for study programs that have participated in implementing the Independent Campus Learning Program (MBKM).Methodology/approach: This study uses a qualitative descriptive research method with observations and interviews with students who have carried out teaching assistance in an Independent Campus Learning Program.Results/findings: This study found that the implementation of teaching assistance for the Merdeka Belajar Campus Merdeka program with the aim of improving learning and the quality of graduates in its implementation was quite good. This is proven by the experience of students who gained experience in teaching, controlling the class, preparing syllabi and lesson plans, preparing learning media, and carrying out work programs that must be achieved during the program.Limitations: The obstacles in implementing Merdeka Belajar Campus Merdeka include socialization and interaction with students' understanding of teaching assistance and support program facilities that are not yet optimal.Contribution: This research is useful as an input and material for improving the system for implementing teaching assistance for the Independent Campus Learning Program (MBKM) to improve it in the future.